Surface support capabilities of freshly sprayed fibre reinforced concrete and safe re-entry time for underground excavations. (April 2017) - Saw, Hla Aye; Villaescusa, Ernesto; Windsor, Christopher R.; Thompson, Alan G.
Highlights: 1 MPa UCS value is the benchmark for a safe re-entry into freshly sprayed concrete. This research utilises shear strength as a guideline for safe re-entry. Abstract: Sprayed fibre reinforced concrete support is an important component of modern ground support schemes used for stabilisation of underground excavations in rock. In particular, the safe re-entry time after fibre reinforced concrete has been sprayed needs to be considered as it influences the productivity associated with development rates. It is proposed here that the shear strength of the sprayed fibre reinforced concrete matrix is a better parameter to consider than the Uniaxial Compressive Strength of the overall sprayed fibre reinforced concrete material including coarse aggregates. Consequently, a number of sprayed fibre reinforced concrete paste mixes were prepared and evaluated for strength gain. It was found generally that the shear strength of sprayed fibre reinforced concrete pastes increase exponentially during the first 4 h of curing in all sprayed fibre reinforced concrete mixes, except when the pastes included a hydration stabiliser. It was found for sprayed fibre reinforced concrete mixes with accelerator, synthetic fibres and aggregates that an average layer of about 50 mm thickness develops sufficient shear strength of about 20 kPa within about one hour to support the layer mass and a tetrahedral block with 1 m edge lengths. For the same sprayed fibre reinforced concrete layer, it was found that the sprayed fibre reinforced concrete layer and a cubic metre block can be supported within about 3 h and 50 min when the sprayed fibre reinforced concrete shear strength is estimated to be approximately 97 kPa.